Effect of sodium-glucose Co-transporter 2 inhibitors on MCP-1 and uromodulin levels in patients with type 2 diabetes mellitus - Mani Pathak; Haya Majid; Parvej Khan; Md Masoom; Rizwana Parveen; Prem Kapur; Sunil Kohli; Nidhi (Clinical Epidemiology and Global Health)
Background and aim: A class of anti-diabetic medications, namely Sodium Glucose Co-Transporter-2 (SGLT2) inhibitors, has shown their potential effects beyond glucose tolerance in Type 2 Diabetes Mellitus (T2DM) patients. These inhibitors may affect inflammatory indicators, including monocyte chemoattractant protein-1 (MCP-1), which contributes to insulin resistance and vascular inflammation. Furthermore, uromodulin levels, a kidney-specific protein linked to renal function and tubular health, may be impacted by SGLT2 inhibitors. The study aimed to assess the role of inflammatory biomarkers in patients with renal dysfunction and T2DM who were receiving SGLT2 inhibitors compared to those receiving antidiabetic medications other than SGLT2 inhibitors. Methodology: It was a cross-sectional, observational, prospective, and single-centric study that was done to assess serum MCP-1 and uromodulin levels in T2DM patients with early renal dysfunction on SGLT2 inhibitors (n = 28), other antidiabetic medications (n = 28), and healthy controls (n = 30). The study also evaluated associations with glycosylated hemoglobin (HbA1c), fasting plasma glucose (FPG), estimated glomerular filtration rate (eGFR), serum creatinine, serum urea, serum uric acid, body mass index (BMI), and age. Results: Serum MCP-1 and uromodulin levels were considerably lower in T2DM patients with early renal impairment who were on SGLT2 inhibitors than in those taking other antidiabetic drugs. Serum uromodulin was found to be negatively correlated with both serum urea and FPG in patients using SGLT2 inhibitors. FPG and serum MCP-1 were significantly correlated negatively in these patients. However, no significant correlation was observed between serum MCP-1 and HbA1c, eGFR, serum creatinine, or serum uric acid. Conclusion: It has been concluded that patients taking SGLT2 inhibitors are at lower risk of inflammation and renal dysfunction. However, further research is needed to strengthen the evidence of the associations between SGLT2 inhibitors and inflammation.